MINOCA: The caveat of absence of coronary obstruction in myocardial infarction - Nousjka P.A. Vranken; Tobias F.S. Pustjens; Evelien Kolkman; Renicus S. Hermanides; Sebastiaan C.A.M. Bekkers; Martijn W. Smulders; Yvonne J.M. van Cauteren; Jordi Heijman; Saman Rasoul; Jan P. Ottervanger; Arnoud W.J. van 't Hof (International Journal of Cardiology: Heart & Vasculature, 2020)
Aims: Whether patients with MINOCA (myocardial infarction with non-obstructive coronary arteries) have better outcomes than patients with obstructive coronary artery disease remains contradictory. The current study focussed on the clinical profile and prognosis of MINOCA patients. Methods and results: We performed a retrospective analysis of patients with acute coronary syndrome (ACS) admitted to the Isala hospital in Zwolle, the Netherlands, between 2006 and 2014. A total of 7693 patients were categorized into three groups: MINOCA, single-vessel obstructive ACS (SV-ACS), and multi-vessel obstructive ACS (MV-ACS). MINOCA patients (5.2% of the total population) were more likely to be female (51.5% vs. 30.3% and 26.0% in SV-ACS and MV-ACS, respectively, p < 0.001 for both). The prevalence of risk factors in the MINOCA group was in between the SV-ACS and MV-ACS groups. Logistic regression revealed a lower odds of dying in SV-ACS (odds ratio (OR) = 0.70 (p = 0.04)) and a similar odds in MV-ACS (OR = 0.88, p = 0.45) compared to MINOCA. Conclusions: Patients with MINOCA show an ‘intermediate’ risk profile with mortality rates in between those of both ACS groups. Hence, MINOCA should be recognised as a potential risk factor for mortality, requiring adequate treatment and follow-up.